Faire et se faire : les ressorts d’une vie éthique enseignante cohérente - Alfred Romuald Gambou (Recherches en Éducation)
From a theoretical anchoring backed by our own experiential experience, this research attempts to understand to what extent the double concern for modalities and coherence allows teaching practice, the ethics that constitute it, to to be its own end in itself and to direct existence towards its own goals? Insofar as this teaching practice is based on three springs identified here, which in the face of the injunctions resulting from an instrumental rationality, make possible the emergence and the growth of a coherent teaching ethical life. It emerges that the historical understanding of one's being, this self-knowledge by oneself, articulated with the in-depth knowledge of the theoretical fields because they are the ones who in the field produce the observables, and the experience in the sense of John Dewey as long as 'it allows the observation of the connections implied between the actions, the events and the facts, revitalizes the acting teacher. Thus, to the prescriptive question "What should I do?" based on a quantifiable, controllable and controllable approach, emerges here the non-prescriptive one that takes into account the unforeseen or the unavailable in moral action: “How should I live? my life as a teacher.